A rare presentation of gastric outlet obstruction (GOO) – The Bouveret's syndrome. Issue 1 (March 2015) - kalwaniya, Dheer singh; Arya, S.V.; Guha, Soumya; Kuppuswamy, Manigandan; Chaggar, Jasneet G.; Ralte, Lalmalsamwe; Chejera, Rajkumar; Sharma, Ashok
Abstract: Introduction: Bouveret's Syndrome is a rare cause of Gastric outlet obstruction (GOO) caused by a gall stone which has migrated into the duodenal bulb from a bilioduodenal fistula. It is an uncommon condition and only a few cases have been reported in the medical literature till to date. Presentation of case: We report a case of a 45 year old woman who presented to us with recurrent pain in the upper abdomen for the last 8 years, and that progressed to develop symptoms of gastric outlet obstruction. An upper gastrointestinal endoscopy revealed duodenal ulceration with a stony hard lesion in the first part of duodenum. An contrast enhanced computed tomography (CECT) scan of the abdomen performed later confirmed the presence of cholecystoduodenal fistula and a gall-stone in proximal jejunum. Discussion: Bouveret's syndrome is a case of gastric outlet obstruction caused by the impaction of a large gall stone in the duodenum as a result of a cholecystoduodenal fistula. It constitutes 1–3% of cases of gall stone ileus which in turn complicates only 0.3–4% cases of cholelithisasis. Bouveret's syndrome is managed surgically. Conclusion: Bouveret's syndrome being an uncommon condition may pose a difficulty in diagnosis and dilemma in managing such patients. An awareness is hence essential. Highlights: Bouveret's Syndrome is an uncommon cause of Gastric outlet obstruction (GOO) caused by a gall stone which has migrated into the duodenal bulb from a bilioduodenal fistula. Case of cholelithiasis with presentation of GOO must raise a high index of suspicion. We report a case of a 45 year old woman who presented to us with recurrent pain upper abdomen for last 8 years that progressed to develop symptoms of gastric outlet obstruction. Upper Gastrointestinal endoscopy revealed duodenal ulceration with stony hard lesion in the first part of duodenum. CECT abdomen done later confirmed the presence of cholecystoduodenal fistula and gall stone in proximal jejunum. Enterolithotomy and the pylorus preserving gastrojejunostomy with cholecystectomy was performed in this patient. We have tried to show that there is no gold standard principle laid down for the management of Bouveret's syndrome as it depends on the site of lodgement of stone, the pathological outcome due to its presence and the anatomical distortion.